The Effect of Guided Imagery-Relaxation Technique on The Intensity of Pain In Adolescent with Primary Dysmenorrhea - Yayat Suryati; Nissa Agustin (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2018)
The incidence of dysmenorrhea cases in Indonesia was about 45-95% and 70-90% of cases occurred in adolescence. There are two types of treatment for dysmenorrhoea, namely pharmacological and non-pharmacological therapy. One of the non-pharmacological techniques is guided imagery by doing relaxation. The purpose of this study is to assess the effect of guided imagery on dysmenorrhoea intensity in adolescents. The research applied the quasi-experiment design with the one-group pretest-posttest design. The samples were students of Cimahi senior high school. The samples were chosen using purposive sampling technique. There were 28 respondents involved in this study. The data collection was performed by measuring the scale of pain with the Numeric Rating Scale and then giving intervention of guided imagery- relaxation technique. The interventions were applied base on the standard operating procedure. Intervention is done once a day on the first day of the menstruation period. The data were analyzed using univariate analysis and bivariate analysis. The univariate measured median of data and bivariate applied the Wilcoxon test. The univariate analysis found that the median before the result of dysmenorrhea pain scale before guided imagery- relaxation technique was 5.00 and after the interventions were 2.50. The statistical test found P value of 0,000 <α (0,05). The finding found Ha failed and rejected, it means there was an influence of guided imagery- relaxation technique on the pain intensity in adolescents with dysmenorrhea. It is expected that health institutions share this finding and apply this method to help the adolescent in dealing with dysmenorrhea. Keywords: Adolescent, Dysmenorrhea, Guide Imagery, Relaxation.